Non-insulin-dependent (type II) diabetes mellitus. - Rodger, W (1991)
Non-insulin-dependent (type II) diabetes mellitus is an inherited metabolic disorder characterized by hyperglycemia with resistance to ketosis. The onset is usually after age 40 years. Patients are variably symptomatic and frequently obese, hyperlipidemic and hypertensive. Clinical, pathological and biochemical evidence suggests that the disease is caused by a combined defect of insulin secretion and insulin resistance. Goals in the treatment of hyperglycemia, dyslipidemia and hypertension should be appropriate to the patient's age, the status of diabetic complications and the safety of the regimen. Nonpharmacologic management includes meal planning to achieve a suitable weight, such that carbohydrates supply 50% to 60% of the daily energy intake, with limitation of saturated fats, cholesterol and salt when indicated, and physical activity appropriate to the patient's age and cardiovascular status. Follow-up should include regular visits with the physician, access to diabetes education, self-monitoring of the blood or urine glucose level and laboratory-based measurement of the plasma levels of glucose and glycated hemoglobin. If unacceptably high plasma glucose levels (e.g., 8 mmol/L or more before meals) persist the use of orally given hypoglycemic agents (a sulfonylurea agent or metformin or both) is indicated. Temporary insulin therapy may be needed during intercurrent illness, surgery or pregnancy. Long-term insulin therapy is recommended in patients with continuing symptoms or hyperglycemia despite treatment with diet modification and orally given hypoglycemic agents. The risk of pancreatitis may be reduced by treating severe hypertriglyceridemia (fasting serum level greater than 10 mmol/L) and atherosclerotic disease through dietary and, if necessary, pharmacologic management of dyslipidemia. Antihypertensive agents are available that have fewer adverse metabolic effects than thiazides and beta-adrenergic receptor blockers. New drugs are being developed that will enhance effective insulin secretion and action and inhibit the progress of complications.